Enhancing patient outcomes: the role of clinical utility in guiding healthcare providers in curating radiology AI applications - Franziska Lobig; Jacob Graham; Apeksha Damania; Brian Sattin; Joana Reis; Prateek Bharadwaj (Frontiers in Digital Health, 2024)
With advancements in artificial intelligence (AI) dominating the headlines, diagnostic imaging radiology is no exception to the accelerating role that AI is playing in today's technology landscape. The number of AI-driven radiology diagnostic imaging applications (digital diagnostics) that are both commercially available and in-development is rapidly expanding as are the potential benefits these tools can deliver for patients and providers alike. Healthcare providers seeking to harness the potential benefits of digital diagnostics may consider evaluating these tools and their corresponding use cases in a systematic and structured manner to ensure optimal capital deployment, resource utilization, and, ultimately, patient outcomes—or clinical utility. We propose several guiding themes when using clinical utility to curate digital diagnostics.